Progress and Challenge of Optical Remote Sensing Inversion on Soil Moisture - QIN Xiangdong; PANG Zhiguo; JIANG Wei (Renmin Zhujiang)
Soil moisture is an important parameter for influencing the land surface rainfall and runoff,and a key parameter for understanding the interaction of water and energy between the earth and the atmosphere.Monitoring of this parameter is of great significance to agricultural development and water resources management.As the main means for large-scale monitoring of soil moisture,the remote sensing inversion has received much attention in many studies in terms of method and accuracy.Among them,the research of optical remote sensing inversion on soil moisture lasts the longest,and many inversion methods have been developed currently.In order to sort out these inversion methods,this paper summarizes the commonly used remote sensing data for optical inversion on soil moisture at first,then classifies the inversion methods into reflectivity method,index method and thermal inertia method according to the different objects that correlates with soil moisture in the method and explains their principles,advantages,disadvantages and research progress,and finally discusses the main problems faced by the current optical remote sensing inversion methods as follow:The inversion methods are seriously affected by cloud and fog weather.The effective depth of soil moisture obtained by the inversion method is limited.The inversion methods take insufficient account of land surface heterogeneity.